The Managerial Implications of Positive and Normative Accounting Theories - Ömer Kavrar (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Managers as decision makers need to know the relationship between the accounting procedures and the tools that influence the accounting reports such as stock and bond prices. By doing so, managers need to consider accounting theories which provide the such complex relationships by using large numbers of observations and carefully constructed empirical tests. The two leading theories placed in the accounting literature are positive and normative accounting theories. This study seeks to provide a critical examination and assessment about these two theories from manager’s point of view. The hypotheses discussed include those to which Watts and Zimmerman responded and as well as several other critiques based on managerial implications. This paper also comprises multifarious discussions that are related to the manager implications, made by the well-known accounting theory researchers.